Analysis of the Relationship of Islamic Education in Terms of National Regulations and Madrasah Aliyah Regulations: An Explanatory Sequential Study - Ade Imun Romadan; Abdul Hamid Bashori; Fathi Ben Slama; Nurmalina Nurmalina (STAI Publisistik Thawalib Jakarta, 2026)
This study identifies the lack of a comprehensive comparative analysis on the alignment between national Islamic education regulations and their implementation in internal school policies at Madrasah Aliyah Al-Khairiyah Citangkil, including related implementation challenges. It aims to assess the level of implementation of national Islamic education regulations within the school’s internal framework. The research applies an explanatory sequential design, combining quantitative and qualitative methods in stages. The t-test results show a t-value of 7.864, which exceeds the t-table value of 1.99, indicating a positive, significant effect of the independent variable. The coefficient of determination (R² = 0.442) shows that 44.2% of the variation is explained by the model. These findings suggest that integrating curriculum and religious practices significantly supports the development of students’ religious character, discipline, and responsibility. There is strong integration between religious instruction and daily worship, fostering a consistent religious culture among students. Participation in activities such as Qur’an reading, the Duha prayer, and Arabic use is high and stable. The implementation of Islamic education is reflected in the synergy between structured learning and habitual practice, fostering students’ holistic, integrated cognitive, affective, and psychomotor development. In conclusion, Islamic education regulations are effectively implemented through curriculum integration, the cultivation of worship habits, and character strengthening. This study supports the development of Islamic education policy and offers recommendations for aligning national regulations with school practices.